2015
DOI: 10.4103/0973-1482.147727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dose perturbation at the interface of two different density medium using GAFCHROMIC film EBT2 and Monte Carlo code EGSnrc for Co-60 beam

Abstract: We observed significant variation in dose for smaller fields. There is a dose build down in the backward region and a dose build up in the forward direction. In the region of electronic disequilibrium, dose reduction near interface (proximal end) will have negative impact if target region is embedded there, on the contrary, it would be beneficial if there is normal tissue/critical organ adjacent to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on the previous studies, MC simulation has been considered to be the most accurate tool to describe the underlying physical interactions between radiation and matter. EGSnrc MC Software has been successfully used in various dosimetry principles,[ 12 13 ] HVL evaluation of orthovoltage machine,[ 14 ] simulation of radiotherapy treatment units,[ 15 16 17 18 ] beam quality correction factor,[ 19 ] and so forth. Furthermore, previous studies have shown that MC can be used in the evaluation of X-rays transmission through some shielding materials,[ 11 ] evaluation of the attenuation coefficient of personal radiation shielding protective clothing,[ 20 ] determination of shielding properties of concrete,[ 21 ] shielding analysis,[ 22 ] and the simulation of X-ray room shielding in diagnostic radiology.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies, MC simulation has been considered to be the most accurate tool to describe the underlying physical interactions between radiation and matter. EGSnrc MC Software has been successfully used in various dosimetry principles,[ 12 13 ] HVL evaluation of orthovoltage machine,[ 14 ] simulation of radiotherapy treatment units,[ 15 16 17 18 ] beam quality correction factor,[ 19 ] and so forth. Furthermore, previous studies have shown that MC can be used in the evaluation of X-rays transmission through some shielding materials,[ 11 ] evaluation of the attenuation coefficient of personal radiation shielding protective clothing,[ 20 ] determination of shielding properties of concrete,[ 21 ] shielding analysis,[ 22 ] and the simulation of X-ray room shielding in diagnostic radiology.…”
Section: Discussionmentioning
confidence: 99%